Assessment of soil redistribution rates in a Mediterranean olive orchard in South Spain using two approaches: 239+240Pu and soil erosion modelling - García-Gamero, Vanesa; Mas, J.L.; Peñuela, Andrés; Hurtado, Santiago; Peña, Adolfo; Vanwalleghem, Tom (Catena (Giessen), 2024)
•We compare soil redistribution rates estimated by both 239+240Pu and WaTEM/SEDEM.•Rates estimated by the two methods show important discrepancies.•These discrepancies help us understand the limitations of each method.•Less uncertain conditions are needed to validate the 239+240Pu method.•Both methods predict severe soil degradation in the next decades. Soil redistribution by water and tillage soil erosion has a profound effect on the spatial variability of soil security indicators. In this study, we assess the potential of estimating long-term soil redistribution rates across a Mediterranean olive orchard catchment using two methods: 239+240Pu and the WaTEM/SEDEM model. Additionally, we identify potential sources of uncertainty explain result discrepancies, and offer guidance for reducing uncertainty. Soil sampling points were taken both in the inter-row areas and below the tree canopies and 239+240Pu inventories were converted into soil redistribution rates using MODERN. Sediment yield data measured in the catchment outlet is used to calibrate WaTEM/SEDEM. The results show a poor agreement between both methods. In this sense, these results indicate that both methods are considerably affected by several sources of uncertainty, both inherent to the methods themselves and related to the specific conditions of the study area. The latter are mainly related to anthropogenic changes in the soil surface related to soil tillage and rill filling practices and an important past land leveling effect. Despite the discrepancies, both methods convey a similar overarching message: soil security and olive production can be highly threatened in the Mediterranean in the next decades. This study demonstrates the potential advantages of combining FRN-based estimates and model simulations and highlights the importance of selecting an appropriate study area in this type of studies and the need to recognize associated uncertainties when estimating soil redistribution rates, whether employing FRN-based or modelling methods.